Civil Rights of the Believers of Unofficial Religions (Penghayat Kepercayaan) in Pekalongan District - Moh. Ilham A Hamudy; M Saidi Rifki (Universitas Andalas, 2020)
There are seven groups of unofficial religions (penghayat kepercayaan) in Pekalongan District. The issuance of Constitutional Court (MK) decision No. 97/ PUU-XIV/2016 did not automatically fulfill their civil rights. There were various obstacles to implement the constitutional court decision. Therefore, this study specifically aimed to review their existence and the fulfillment of their civil rights after the Constitutional Court's decision. With a qualitative approach, and descriptive and literature methods, this study found that the social access of penghayat kepercayaan, such as the inclusion of their beliefs in the religion part of the Identity Card (